Ácido cítrico sostenible a partir de los residuos agroindustriales. El caso de Diana Food Ecuador S.A. - Rojas Romero, Edison Kelvin; Araujo Barzallo, Maria Jose (Machala : Universidad Técnica de Machala, 2023)
The main objective of this degree work is to analyze the viability of producing sustainable citric acid from the waste generated in the Diana Food production process. The research is framed in the circular economy and seeks to evaluate the economic, social and environmental aspects of this proposal in the province of El Oro, Ecuador. The methodology used is applied, with a systemic approach and a deductive method. The research technique used is the study of documents, specifically content analysis. The results obtained reveal that Ecuador imports a significant amount of citric acid, mainly from China, which poses challenges in terms of economy and food security. The sustainable production of citric acid from agro-industrial waste could reduce dependence on imports and generate local employment, aligning with global trends towards sustainability. Collaboration between industry, academia and authorities stands out as a key element in this process. Each of these actors plays a fundamental role: the industry provides experience and resources, academia carries out rigorous research, and authorities establish standards and regulations to guarantee product safety and quality. The need for accurate evaluation and the promotion of research and collaboration between different actors is underlined. The sustainable production of citric acid from agroindustrial waste is a proposal with potential, but its success will depend on overcoming technical challenges and establishing collaborations between different sectors.
El presente trabajo de titulación tiene como objetivo principal analizar la viabilidad de producir ácido cítrico sostenible a partir de los residuos generados en el proceso productivo de Diana Food. La investigación se enmarca en la economía circular y busca evaluar los aspectos económicos, sociales y ambientales de esta propuesta en la provincia de El Oro, Ecuador. La metodología empleada es de tipo aplicada, con un enfoque sistémico y un método deductivo. La técnica de investigación utilizada es el estudio de documentos, específicamente el análisis del contenido. Los resultados obtenidos revelan que Ecuador importa una cantidad significativa de ácido cítrico, principalmente de China, lo que plantea desafíos en términos de economía y seguridad alimentaria. La producción sostenible de ácido cítrico a partir de residuos agroindustriales podría reducir la dependencia de las importaciones y generar empleo local, alineándose con tendencias globales hacia la sostenibilidad. La colaboración entre la industria, la academia y las autoridades se destaca como un elemento clave en este proceso. Cada uno de estos actores desempeña un papel fundamental: la industria aporta experiencia y recursos, la academia realiza investigaciones rigurosas y las autoridades establecen estándares y regulaciones para garantizar la seguridad y calidad del producto. Se subraya la necesidad de una evaluación precisa y el fomento de la investigación y la colaboración entre los diferentes actores. La producción sostenible de ácido cítrico a partir de residuos agroindustriales es una propuesta con potencial, pero su éxito dependerá de superar los desafíos técnicos y establecer colaboraciones entre los diferentes sectores.
Keywords: ACIDO CITRICO; AGROINDUSTRIA; RESIDUOS; ECONOMIA CIRCULAR